Impact of dairy hubs on smallholder welfare: Empirical evidence from Kenya - Vincent Ngeno (Agricultural and Food Economics, 2018)
This paper identifies the factors that affect farmers' decision to participate in a dairy hub. It also examines the impacts of dairy hub participation on rural household welfare measured by farm yields and net returns in Kenya. The study utilises farm-level data of 826 Kenyan small-scale dairy farmers. The casual impact of dairy hub participation is estimated by utilising endogenous switching regression. This helps in estimating the true welfare effect of dairy hub participation by controlling the role of selection problem on participation decision. The empirical results indicate that farmers' education, extension services, credit access, landholding, tropical livestock unit, distance to dairy hub, off-farm work and household size mainly determine participation in dairy hub. It was also found that dairy hub participation significantly increases yields and net returns.
Keywords: 330; Household welfare; Dairy hub participation; Impact assessment; Endogenous switching